Mitraguna Product Marketing Strategy with Murabahah Agreement at BSI KCP Rogojampi Banyuwangi - Mira Rahayu; Nur Anim Jauhariyah (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
The Mitraguna Berkah BSI KCP Rogojampi financing product is one of the products that customers are interested in. This research aims to determine the marketing strategy for Mitraguna products at BSI KCP Rogojampi in increasing the number of customers and to find out the obstacles and solutions faced in implementing the marketing strategy for Mitraguna products. The research method used used a qualitative approach with employee informants at BSI KCP Rogojampi and then analyzed using SWOT. The results of this research state that the marketing strategy for Mitraguna financing at BSI KCP Rogojampi uses the 7P marketing mix, namely Product, Price, Promotion, and Place, People, Process, Physical Evidence. The obstacle faced is that price competition between banks is very competitive because many other banks have similar products but offer different prices, making price competition very tight. The strategies used include conducting face to face and door to door promotions and intensively contacting customers by offering competitive prices and in accordance with sharia principles.